(untitled) (Scientia Agricola, 2013)
Sugarcane (Saccharum spp.) is an efficient and sustainable alternative for energy generation compared to non-renewable sources. Currently, during the mechanized harvest process, the straw left in the field can be used in part for the second generation ethanol and increasing the electric energy production. Thus, this study aimed to provide information on the potential for residual biomass cultivars of sugarcane cropping system. This study provides the following information: yield of straw, depending on the calculated leaf area index and the number of tillers per linear meter; primary energy production of several sugarcane genotypes; contribution of dry tops and leaves; biomass yield; and evaluation of fiber, cellulose, hemicellulose and lignin. Preliminary results obtained by researchers of the State of São Paulo, Brazil, and reCviews related studies are presented. The results suggest that the production of sugarcane straw content varies according to the cultivars; the greater mass of sugarcane straw is in the top leaves and that the potential for the crude energy production of sugarcane per area unit can be increased using fiber-rich species or species that produce more straw. The straw indexes was shown to be a good indicator and allow the estimation of straw volumes generated in a sugarcane crop. The cellulose, hemicellulose and lignin composition in sugarcane is distinct among varieties. Therefore, it is possible to develop distinct biomass materials for energy production and for the development of sugarcane mills using biochemical processes and thermal routes.